Business Management Strategy and Customer Loyalitas to Service Quality at Titia Gallery During the Covid 19 Period - Diana Novita; Merita Yanita (Jurnal Tata Rias dan Kecantikan, 2022)
The research was motivated byithe effects of the covid-19 virus felt by Titia Gallery Bukittinggi with many clients delaying receptions until the cancellation of service use. The better the quality of service, the greater the customer satisfaction. The research aims to a) describe the business management strategy at Titia Gallery on service quality during the Covid- 19 period. b) describe customer loyalty to the quality of service at Titia Gallery during the Covid-19 period. c) describe the business management strategy and customer loyalty at Titia Gallery on service quality during the Covid-19 period. The type of research study is descriptive- quantitative. A total of 9 Titia Team members and 71 customers are the Population. Mechanism of sampling with purposive sampling method. The number of samples in this study were 80 respondents. Collecting data using interview, observation, documentation, and distribution of questionnaires in theiform of a Likert scale which is tested for validity and reliability. The analyticalitechnique applied is descriptive analysis, normality test, hypothesis testing consisting of t test, simultaneous f test, and R2 test. The results for the effect of the makeup business management strategy on service quality are 0.431 with no significant effect category, the results of the frequency distribution are 98.75%, the value of the influence of customer loyalty on service quality is 0.00 with a significant effect category, the frequency distribution is 71.25%. The r2 test value is 24.9% where the makeup business management strategy and customer loyalty have a simultaneous effect on service quality. For further researchers, it is recommended to develop similar things in the makeup business management strategy in order to survive.